2020
DOI: 10.1002/dvg.23401
|View full text |Cite
|
Sign up to set email alerts
|

Ray flower initiation in the Helianthus radula inflorescence is influenced by a functional allele of the HrCYC2c gene

Abstract: The radiate pseudanthium, with actinomorphic disk flowers surrounded by showy marginal zygomorphic ray flowers, is the most common inflorescence in the Helianthus genus. In Helianthus radula, ray flower primordia are normally absent at the dorsal domain of the inner phyllaries (discoid heads) while the occurrence of radiate inflorescences is uncommon. In Helianthus spp., flower symmetry and inflorescence architecture are mainly controlled by CYCLOIDEA (CYC)-like genes but the putative role of these genes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…However, Fambrini et al (2014) discovered that the insertion of the TE in HaCYC2c promoter does not always lead to ectopic expression and shift toward zygomorphic florets, suggesting that the regulation of flower type identity is much more complexand genotype-specific. In sunflower, discoid capitula are found in Helianthus radula, a species widespread in the southeast of the United States (Mason et al, 2015;Fambrini et al, 2020). Although H. radula occasionally forms ray florets, they are few and tiny, and not comparable to any other Helianthus species (Heiser et al, 1969;Fambrini et al, 2020).…”
Section: Regulation Of Ray Floret Identitythe Role Of Cycloidealike G...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Fambrini et al (2014) discovered that the insertion of the TE in HaCYC2c promoter does not always lead to ectopic expression and shift toward zygomorphic florets, suggesting that the regulation of flower type identity is much more complexand genotype-specific. In sunflower, discoid capitula are found in Helianthus radula, a species widespread in the southeast of the United States (Mason et al, 2015;Fambrini et al, 2020). Although H. radula occasionally forms ray florets, they are few and tiny, and not comparable to any other Helianthus species (Heiser et al, 1969;Fambrini et al, 2020).…”
Section: Regulation Of Ray Floret Identitythe Role Of Cycloidealike G...mentioning
confidence: 99%
“…In sunflower, discoid capitula are found in Helianthus radula, a species widespread in the southeast of the United States (Mason et al, 2015;Fambrini et al, 2020). Although H. radula occasionally forms ray florets, they are few and tiny, and not comparable to any other Helianthus species (Heiser et al, 1969;Fambrini et al, 2020). Fambrini et al (2020) showed that a functional allele of HrCYC2c gene is necessary, but not sufficient, for ray initiation.…”
Section: Regulation Of Ray Floret Identitythe Role Of Cycloidealike G...mentioning
confidence: 99%
“…Fambrini et al isolated three CYC2 subclade genes ( HrCYC2c , HrCYC2d , and HrCYC2e ) associated with the identity of the Helianthus ray–floret (Hr), among which HrCYC2c played an important role in the initiation of the ray floret primordium [ 38 ]. The capitula of HrCYC2c -mutant homozygous dominant plants ( HrCYC2c / HrCYC2c ) and heterozygous dominant plants ( HrCYC2c / HrCYC2c-m ) initiated ray florets, whereas the recessive homozygous plants ( HrCYC2c-m / HrCYC2c-m ) did not develop ray florets [ 38 ].…”
Section: Progress In Research On Cyc -Like Genes I...mentioning
confidence: 99%
“…In different evolutionary lineages, gene duplication events occurred in each branch at different time points during evolution [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ], as shown in Figure 1 . A more thorough analysis of the CYC2 subgroup confirmed that they are key regulatory genes for the bilateral symmetry of flowers [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has central (usually bisexual) disc florets and peripheral conspicuous (usually female) ray florets. Other types, such as the discoid head (with only bisexual disc florets) and the disciform head (discoid-like, but with a few female asymmetric marginal florets) are scattered across the phylogeny of the family (Bello et al, 2013;Chen et al, 2018;Fambrini et al, 2020;Funk et al, 2009;Harris, 1995Harris, , 1999Jeffrey, 2009;Leppik, 1970).…”
Section: Introductionmentioning
confidence: 99%